Avaliação de parâmetros laboratoriais de pacientes com diagnóstico de COVID-19 do Hospital Risoleta Tolentino Neves - Alice Aparecida Lourenço (2021)
The pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an emerging crisis affecting the public health system. The clinical features of COVID-19 can range from an asymptomatic state to acute respiratory syndrome and multiple organ dysfunction. Some hematological and biochemical parameters can help predict the clinical outcome with COVID-19. This study aims to evaluate hematological and biochemical parameters of patients diagnosed with COVID-19 at Hospital Risoleta Tolentino Neves, in Belo Horizonte, Minas Gerais. Patients included in the study had a diagnosis of SARS-CoV-2 infection confirmed by RT-PCR, and biochemical and hematological measurements were performed by the Hospital Risoleta Tolentino Neves laboratory and were made available for this study. A biorepository with blood samples without anticoagulant (serum), blood with anticoagulant (EDTA) and tracheal aspirate from patients with COVID-19 at Hospital Risoleta Tolentino Neves for future studies. For the statistical analysis of the data, the GraphPad Prism 8.0 software (GraphPad Software Inc.) was used to compare the groups. Among the parameters evaluated, the ones that stood out the most with performance greater than or equal to 0.70 and that can be used as possible biomarkers for the severity of the patient with COVID-19 are: global leukocytes, neutrophils, neutrophil/lymphocyte sodium ratio, chlorine, lactate, and urea. These parameters had their values increased in critically ill patients, especially in the third time of collection, with emphasis on urea, which showed a performance of 0.84 at later times in the follow-up of patients. These results indicate the importance of laboratory monitoring combined with the clinical aspects of patients with COVID-19 in this unique cohort that exhibited high mortality.